2019
DOI: 10.1126/sciadv.aau9413
|View full text |Cite
|
Sign up to set email alerts
|

Forty years of reform and opening up: China’s progress toward a sustainable path

Abstract: After 40 years of reform and “opening up,” China has made remarkable economic progress. Such economic prosperity, however, has been coupled with environmental degradation. We analyze diverse long-term data to determine whether China is experiencing a decoupling of economic growth and environmental impacts, and where China stands with respect to the Sustainable Development Goals (SDGs) in terms of reducing regional division, urban-rural gap, social inequality, and land-based impacts on oceans. The results highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 265 publications
(137 citation statements)
references
References 48 publications
2
110
0
Order By: Relevance
“…For instance, in 1978 the Chinese government began to comprehensively adjust the development direction of the national economy from a planned economy to a socialist market economy. As a result, China's economic efficiency gradually improved from the restrictive economic system affected by the Cultural Revolution (11). During the first 3 y of reform (1978 to 1980), the economic growth rate was significantly higher than the growth rate of energy consumption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in 1978 the Chinese government began to comprehensively adjust the development direction of the national economy from a planned economy to a socialist market economy. As a result, China's economic efficiency gradually improved from the restrictive economic system affected by the Cultural Revolution (11). During the first 3 y of reform (1978 to 1980), the economic growth rate was significantly higher than the growth rate of energy consumption.…”
Section: Resultsmentioning
confidence: 99%
“…There is also a strong coupling relationship between PCG and CO 2 emissions per capita in China (Fig. 1A), and it has been demonstrated that the economic growth remains strongly coupled with CO 2 emissions (11).…”
mentioning
confidence: 96%
“…This has in effect triggered several climate change-related studies across different disciplines. Anthropogenic emissions, the principal factor of climate change, have several causes and dimensions, ranging from energy intensity [8], income level [9,10], greenhouse gas intensity [11], population [12,13], urbanization [14], governance [15], trade [16], technology [17], resource availability [18], industrialization [19], infrastructure [20], development [21], lifestyle and behaviour [22]. Dimensions of emissions range from economic incentives [23], non-climate policies [24], information provision [25], direct regulation [26], awareness creation [25], planning [27], research and development [28].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is widely appreciated that investment, consumption and export are the troika for economic growth, and it is not wise to simply restrain consumption to mitigate the CO 2 emissions [11]. In addition, as reported by a recent study that China's economic prosperity had been coupled with environmental degradation, and suggested that decoupling economic growth from ecological impact had been central to achieve the national sustainable development [12]. Therefore, it is also necessary and imperative for China to discover a green, low-carbon and sustainable path to coordinate the link between developmental and environmental protection [13].…”
Section: Introductionmentioning
confidence: 99%